partitioning of ecosystem respiration in a paludified shallow peat spruce forest in the southern taiga of european russia - J Kurbatova; F Tatarinov; A Molchanov; A Varlagin; V Avilov; D Kozlov; D Ivanov; R Valentini (Environmental Research Letters, 2013)
Soil, tree stems, and ecosystem carbon dioxide fluxes were measured by chambers and eddy covariance methods in a paludified shallow-peat spruce forest in the southern taiga of European Russia (Tver region, 56 N 33 E) during the growing seasons of 2002â€2012. The site was established in 1998 as part of the EUROSIBERIAN CARBONFLUX project, an international field experiment examining atmosphereâ€biosphere interaction in Siberia and European Russia. In all years the observed annual cumulative net ecosystem flux was positive (the forest was a source of carbon to the atmosphere). Soil and tree stem respiration was a significant part of the total ecosystem respiration (ER) in this paludified shallow-peat spruce forest. On average, 49% of the ER came from soil respiration. We found that the soil fluxes exhibited high seasonal variability, ranging from 0.7 to 10 mol m 2 s 1 . Generally, the soil respiration depended on the soil temperature and ground water level. In drought conditions, the soil respiration was low and did not depend on temperature. The stem respiration of spruces grew intensively in May, had permanently high values from June to the end of September, and in October it dramatically decreased. The tree stem respiration in midsummer was about 3â€5 mol m 2 s 1 for dominant trees and about 1â€2 mol m 2 s 1 for subdominant trees. The respiration of living tree stems was about 10â€20% of the ER.